The Pristine Dwarf-Galaxy survey – II. In-depth observational study of the faint Milky Way satellite Sagittarius II. Issue 1 (12th October 2019) - Longeard, Nicolas; Martin, Nicolas; Starkenburg, Else; Ibata, Rodrigo A; Collins, Michelle L M; Laevens, Benjamin P M; Mackey, Dougal; Rich, R Michael; Aguado, David S; Arentsen, Anke; Jablonka, Pascale; González Hernández, Jonay I; et al.
ABSTRACT: We present an extensive study of the Sagittarius II (Sgr II) stellar system using MegaCam g and i photometry, narrow-band, metallicity-sensitive calcium H&K doublet photometry and Keck II/DEIMOS multiobject spectroscopy. We derive and refine the Sgr II structural and stellar properties inferred at the time of its discovery. The colour–magnitude diagram implies Sgr II is old (12.0 ± 0.5 Gyr) and metal poor. The CaHK photometry confirms the metal-poor nature of the satellite ([Fe/H] CaHK = −2.32 ± 0.04 dex) and suggests that Sgr II hosts more than one single stellar population ($σ _[FeH]^CaHK = 0.11^{+0.05}_{-0.03}$ dex). Using the Ca infrared triplet measured from our highest signal-to-noise spectra, we confirm the metallicity and dispersion inferred from the Pristine photometric metallicities ([Fe/H]spectro = −2.23 ± 0.05 dex, $σ _[Fe/H]^spectro = 0.10 ^{+0.06}_{-0.04}$ dex). The velocity dispersion of the system is found to be $σ _{v} = 2.7^{+1.3}_{-1.0} {\rm \, km \, \, s^{-1}}$ after excluding two potential binary stars. Sgr II's metallicity and absolute magnitude ( MV = −5.7 ± 0.1 mag) place the system on the luminosity–metallicity relation of the Milky Way dwarf galaxies despite its small size. The low but resolved metallicity and velocity dispersions paint the picture of a slightly dark-matter-dominated satellite ($M/L = 23.0^{+32.8}_{-23.0}$ M⊙ L$^{-1}_{\odot }$ ). Furthermore, using the Gaia Data Release 2, we constrain the orbit of the satellite and find an apocentre of $118.4 ^{+28.4}_{-23.7} {\rm \, kpc}$ and a pericentre of $54.8 ^{+3.3}_{-6.1} {\rm \, kpc}$ . The orbit of Sgr II is consistent with the trailing arm of the Sgr stream and indicates that it is possibly a satellite of the Sgr dSph that was tidally stripped from the dwarf's influence.